2014
DOI: 10.1021/ma500788n
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Sample Preparation Methods for Dynamic Nuclear Polarization Solid-state NMR of Synthetic Polymers

Abstract: International audienceThis work compares the overall sensitivity enhancements provided by dynamic nuclear polarization (DNP) for the solid-state NMR characterization of polymer samples doped with biradicals and prepared either by film casting (FC), or by glass forming (GF) using 1,1,2,2-tetrachloroethane as the solvent. Analysis of amorphous and semicrystalline polymers (polystyrene, poly(ethylene oxide), polylactide, poly(methyl methacrylate)) of varying molecular weights showed that GF provided larger sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(78 citation statements)
references
References 43 publications
(87 reference statements)
1
77
0
Order By: Relevance
“…However, the situation changes when one is using an organic-solvent-based DNP matrix, such as those already used for a variety of studies [29][30][31][32][33][34][35][36], and/or quadrupolar nuclei [31,[35][36][37][38]. Organic solvents are chosen based on a few criteria: their inertness to the analyte and polarizing agent, the position of their resonances in NMR spectra, their RT vapor pressure, and their physical state at experimental temperatures [39].…”
Section: Obtaining An Enhanced Absolute Sensitivitymentioning
confidence: 99%
See 4 more Smart Citations
“…However, the situation changes when one is using an organic-solvent-based DNP matrix, such as those already used for a variety of studies [29][30][31][32][33][34][35][36], and/or quadrupolar nuclei [31,[35][36][37][38]. Organic solvents are chosen based on a few criteria: their inertness to the analyte and polarizing agent, the position of their resonances in NMR spectra, their RT vapor pressure, and their physical state at experimental temperatures [39].…”
Section: Obtaining An Enhanced Absolute Sensitivitymentioning
confidence: 99%
“…This involves solubilizing both the polarizing agent and the polymer analyte in a co-solvent, with subsequent solvent evaporation. This approach has been revisited recently by Viel and co-workers [72] and also compared to the more common glass-forming approach as well as an impregnation method [33]. It was shown that a consistently higher ASR was returned using a DNP matrix (glass-forming approach) compared to film casting [33].…”
Section: Matrix-free Samplesmentioning
confidence: 99%
See 3 more Smart Citations